Downregulation of aquaporin 3 promotes hyperosmolarity-induced apoptosis of nucleus pulposus cells through PI3K/Akt/mTOR pathway suppression - Sang, Yuan; Zhao, Huiqing; Wu, Jiajun; Zhang, Ting; Xu, Wenbin; Liu, Kaihua; Liu, Chang; Li, Ping; Xu, Yichun; Zhang, Jianying; Hou, Gang (Frontiers in Genetics, 2025)
IntroductionHyperosmolarity plays a crucial role in the apoptosis of nucleus pulposus cells (NPCs) during intervertebral disc degeneration (IVDD). Aquaporin 3 (AQP3), a membrane channel protein, maintains cellular osmotic balance by facilitating the transport of water and osmolytes. While AQP3 downregulation is associated with disc degeneration, its function in apoptosis under hyperosmotic conditions remains unclear.MethodsWe investigated the effects of hyperosmolarity on AQP3 expression and NPC apoptosis in vitro. Furthermore, AQP3 was overexpressed in NPCs using lentiviral vectors, and its function was pharmacologically inhibited. Key markers of the PI3K/AKT/mTOR signaling pathway, mitochondrial function, reactive oxygen species (ROS) accumulation, and apoptosis were assessed. The therapeutic potential of AQP3 was validated in a rat model of IVDD through histological analysis of disc structure.ResultsIn this study, we show that hyperosmolarity leads to a reduction in AQP3 levels, inhibits the PI3K/AKT/mTOR signaling pathway, and triggers mitochondrial dysfunction and the accumulation of ROS in NPCs. Overexpression of AQP3 through lentiviral vectors restores this pathway, mitigates oxidative damage, and decreases apoptosis, thereby preserving disc structure in IVDD rat models. Conversely, pharmacological inhibition of AQP3 worsens extracellular matrix (ECM) catabolism and nucleus pulposus (NP) tissue loss.DiscussionOur findings indicate that AQP3 deficiency under hyperosmotic conditions contributes to NPC apoptosis by suppressing the PI3K/AKT/mTOR signaling pathway, potentially establishing a pathological cycle of disc degeneration. These results highlight AQP3 as a potential therapeutic target for IVDD.